PATIENT UNDERGOING COMBINED RIGHT RADICAL NEPHRECTOMY AND RIGHT ATRIAL TUMOUR EXCISION: ANAESTHETIC MANAGEMENT - Kamath, Manjunath R.; P., Krishna Prasad; Gopalakrishnan, Mundayat; P., Rajeev T. (Journal of Health and Allied Sciences NU, 2011)
We describe anaesthetic management of a rare case of right atrial tumour with right renal mass posted for combined excision of right atrial tumor and right radical nephrectomy. Anaesthesia plan was combined thoracic epidural anaesthesia & general anaesthesia. Right renal mass was removed through the anterior subcostal incision, followed by the right atrial mass excision through the midline sternotomy incision under cardiopulmonary bypass. Issues related to the possibility of inferior vena cava (IVC) thrombus & its extension into the right atrium and the subsequent removal, pain management, ideal position of the central venous access, cardiopulmonary bypass with a single kidney are discussed.
Keywords: Atrial myxoma; Renal cell carcinoma (RCC); IVC thrombus; Cardiopulmonary bypass (CPB)